Acute glutamine supplementation does not affect muscle damage profile after resistance training - Ramallo, B.; Charro, M. A.; Foschini, D.; Prestes, J.; Tania Pithon-Curi, T.; Evangelista, A. L.; Lopes, C. R.; Galatti, L. (International Journal of Sports Science, 2013)
Exercise-induced muscle damage occurs when untrained individuals go through strenuous and/or long-duration physical activities. Aim: to investigate the effects of glutamine supplementation on muscle damage, delayed-onset muscle soreness and muscle strength after a single exercise session in untrained individuals. Metodology: Twenty healthy male subjects with none experience in strength training in the last 12 months were selected and divided into two groups: Maltodextrine (M; n=10) and Maltodextrine plus Glutamine (MGln; n=10) and were submitted to a strength exercise session conducted with multiple sets (a method that uses more than one set per muscular group). The session was performed 72 h after the strength tests. The exercise was for horizontal shoulder adduction (bench press). The subjects performed nine sets of 6-10 maximal repetition at 75% 1-RM (maximum strength test) and rested for 1 min. ANOVA two-way was performed to compare the factors (group and time). When significant differences was indicated by ANOVA, the post-hoc Tukey HSD was performed to identify where differences occurred. In all tests, the level of significance was P < 0.05. Results: Glutamine concentrations significantly increased in group MGln, the change was 36.6% in the time out set training and after training compared to 30` before training\supplementations and 41.46% them compared with M group in the time out set training. Group M showed no significant difference in any time evaluated. (p=0.05). Conclusions: Thus, it can be concluded that the adopted resistance training protocol was efficient in inducing muscle damage, but, glutamine supplementation did not alter the magnitude of the damage.